Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s42003-022-03948-y
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary structure of patient-homogenate amplified α-synuclein fibrils modulates seeding of endogenous α-synuclein

Abstract: Parkinson’s disease (PD) and Multiple System Atrophy (MSA) are progressive and unremitting neurological diseases that are neuropathologically characterized by α-synuclein inclusions. Increasing evidence supports the aggregation of α-synuclein in specific brain areas early in the disease course, followed by the spreading of α-synuclein pathology to multiple brain regions. However, little is known about how the structure of α-synuclein fibrils influence its ability to seed endogenous α-synuclein in recipient cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…The majority of cryo-EM structures of α-Synuclein fibrils resolved to date showed that at least part of the fibril N-terminus is structured, potentially allowing ThT interactions at those sites 12,[70][71][72] . Also there have been previous reports of ThT-negative α-Synuclein fibrils, suggesting that amyloid aggregation alone is not sufficient for ThT signal 73 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cryo-EM structures of α-Synuclein fibrils resolved to date showed that at least part of the fibril N-terminus is structured, potentially allowing ThT interactions at those sites 12,[70][71][72] . Also there have been previous reports of ThT-negative α-Synuclein fibrils, suggesting that amyloid aggregation alone is not sufficient for ThT signal 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Frieg et al [ 43 ] amplified α-synuclein fibrils from brain extracts of patients with pathologically confirmed PD and multiple system atrophy, determined their 3D structures by Cryo-EM, and evaluated their potential to seed α-synuclein related pathology in oligodendrocytes. In the first step, researchers fibrilized α-synuclein by protein misfolding cyclic amplification (PMCA) (see Section 3 ) using brain extracts of patients.…”
Section: α-Synuclein Misfolding Aggregation and Fibrillationmentioning
confidence: 99%
“…The bends of the peptide backbone chain in region H270 and T275 amino acid residues were obtained. The protein compactization led to a decrease of electrostatic repulsion between monomers for subsequent nucleation and growth phase of the amyloid fibril formation process. The stability of the PAP(248–286) monomer folded state was shown with the help of molecular dynamics (MD) simulation.…”
Section: Introductionmentioning
confidence: 99%